Characterisation of Plasmodium falciparum proteins expressed on infected red blood cell surfaces as potential drug targets for severe malaria therapy - Cromarty, Allan Duncan (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2015.